Fast Atom Bombardment Mass Spectral Analysis of Primaquine - N. Sinha, Sukesh (Asian Journal of Chemistry, 2010)
Fast atom bombardment mass spectrometry was used for structure elucidation of primaquine, an antimalarial drug of biomedical interest. m-Nitro-benzyl alcohol was used as a matrix in fast atom bombardment studies because it does not react with analyte to form adduct. The spectra of primaquine clearly indicated that the fragment ions were obtained due to ring cleavages, loss of side chain and proton transfer and free radical rearrangement of molecular ion peak.